Cholesterol-rich lipid-mediated nanoparticles boost of transfection efficiency, utilized for gene editing by CRISPR-Cas9 - Hosseini ES (Dove Medical Press, 2019)
Elaheh Sadat Hosseini,1 Maryam Nikkhah,1 Saman Hosseinkhani21Department of Nanobiotechnology, Faculty of Biological Sciences, Tarbiat Modares University, Tehran, Iran; 2Department of Biochemistry, Faculty of Biological Sciences, Tarbiat Modares University, Tehran, IranPurpose: Gene therapy has become a promising remedy to treat disease by modifying the person’s genes. The therapeutic potential of related tools such as CRISPR-Cas9 depends on the efficiency of delivery to the targeted cells. Numerous transfection reagents have been designed and lots of efforts have been devoted to develop carriers for this purpose. Therefore, the aim of the present study was to develop novel cholesterol-rich lipid-based nanoparticles to enhance transfection efficiency and serum stability.Materials and methods: We constructed two-, three- and four-component cationic liposomes (CLs) to evaluate the combined effect of cholesterol domain and DOPE (dioleoyl phosphatidylethanolamine), a fusogenic lipid, and the PEG (polyethylene glycol) moiety location inside or outside of the cholesterol domain on transfection efficiency and other properties of the particle. Lipoplex formation and pDNA (plasmid DNA) entrapment were assessed by gel retardation assay at different N/P ratios (3, 5, 7). Physicochemical characteristics, cytotoxicity, serum stability and endosomal escape capability of the lipoplexes were studied and transfection potential was measured by firefly luciferase assay. Next, HEK293 cell line stably expressing GFP was utilized to demonstrate the editing of a reporter through Cas9 and sgRNA plasmids delivery by the selected CL formula, which showed the highest transfection efficiency. Results: Among the designed CLs, the four-component formula [DOTAP (1,2-dioleoyl-3-trimethylammoniumpropane)/DOPE/cholesterol/Chol-PEG (cholesterol-polyethylene glycol)] showed the highest rate of transfection at N/P 3. Finally, transfection of Cas9/sgRNA by this formulation at N/P 3 resulted in 39% gene-editing efficiency to knockout GFP reporter. The results also show that this CL with no cytotoxicity effect can totally protect the plasmids from enzymatic degradation in serum.Conclusion: The novel PEGylated cholesterol domain lipoplex providing serum stability, higher transfection efficiency and endosomal release can be used for in vivo Cas9/sgRNA delivery and other future gene-therapy applications.Keywords: cationic liposomes, cholesterol domains, PEGylation, Cas9/sgRNA delivery